Green Investment for Sustainable Business Development: The Influence of Policy Instruments on Solar Technology Adoption - Ali, Shahid; Yan, Qingyou; Irfan, Muhammad; Ameer, Waqar; Atchike, Desire Wade; Acevedo-Duque, Ángel (Frontiers in Energy Research, 2022)
Green investment in sustainable energy can overcome the dependence on fossil fuels worldwide. Renewable energy policies have become the key issue in both developing and developed countries; there is a need to focus on energy-related policies by regulatory authorities of these countries. The current study critically analyzes the performance of the existing renewable energy policy instruments to attract foreign direct investment (FDI) for solar energy development in Pakistan. We evaluate the moderating role of good governance and financial support between the nexus of renewable energy policy instruments and green FDI for the sustainable development of solar energy in the country. The present study used non-probability (purposive) sampling to collect data from 43 respondents (private investors, government officials, energy experts, and policymakers) by conveying an energy policy-related questionnaire survey. The response rate was 82.69%. The study has used partial least squares structural equation modeling to assess formulated hypotheses. The results indicate that the feed-in tariffs is the most effective policy instrument to attract FDI in the country’s solar energy sector. The fiscal measures positively impact the green FDI for solar energy. The results further reveal that good governance and financial support positively and significantly moderate the nexus of renewable energy policy instruments and green FDI for solar energy. The main barriers have been identified over the whole solar energy spectrum. The study findings provide essential policy recommendations and a considerable manual for energy-related regulators, policymakers, and government institutions to adopt advanced renewable energy policy instruments to attract FDI in Pakistan.